Laboratory deinking experiments using mixed office wastepaper, photocopy and laser prints : chemical and enzymatic procedures - Pala, H. (2001)
Paper deinking, either chemical or enzymatic, is known to involve the study of a great number of factors, such that the maximum efficiency of the technique can be achieved. Process modifications are generally related to the type of furnish, namely fibre composition, additives and ink particle characteristics. Experimental routine is usually divided into five different operations: disintegration, pre-cleaning, chemical or enzyme treatment and flotation and/or washing. Each of them contributes differently to the overall process, depending on the sample that is being treated. In the present work, it was our purpose to study and analyse the importance of each phase to achieve the optimal ink removal in different wastepaper samples.